Explaining experiences of punishment and degradation in prisons: a comparative analysis of England & Wales and Norway - Ginneken, Esther F. J. C. van (European journal of criminology, 2025)
There is a consensus in the scholarly literature that imprisonment is a painful and degrading experience. Nevertheless, there is considerable variation across jurisdictions and within countries in prison experiences. In other words, some prisons may be experienced as more degrading and punitive than others. The aims of this article are threefold: first, we establish to what extent experiences of punishment and degradation in prisons in England & Wales and Norway can be attributed to institutional versus individual differences. Second, we examine what factors contribute to experiences of punishment and degradation. Third, we analyse the relationship between institutional (wing) variation in perceived punishment and degradation and self-harming behaviour. Data is used from surveys distributed among individuals incarcerated (N = 1101) in eight prisons in England & Wales and six prisons in Norway. Findings show that prisoners, on average, report experiencing more punishment and degradation on English than Norwegian prison wings, but that there is also substantial variation within each country. Various facets of the prison experience are related to perceived punishment and degradation, such as treatment by staff (i.e., ‘weight’) and imposed restrictions (i.e., ‘depth’). Finally, individuals report more self-harming behaviour when they are incarcerated on wings that are perceived as more degrading and punitive. In conclusion, this shows that surveys can offer insight into the extent to which a prison sentence is experienced as more or less painful, and that this has important implications for the health and well-being of people subjected to it.